Laying the groundwork for embedding AI technologies within organisational ecosystems - Ivchyk, Vasyl (International Center of Scientific Research, 2025)
This study investigates the barriers organizations face in effectively adopting Artificial Intelligence (AI), focusing on psychological, organizational, and ethical challenges. The research aims to develop strategies to reduce resistance, build trust, and support the smooth integration of AI technologies into business operations. Methodology. A qualitative approach was employed, combining an extensive review of existing literature with real-world case studies to identify the root causes of resistance to AI adoption. The study examines psychological fears, organizational obstacles, and ethical concerns, while presenting strategic frameworks and actionable solutions to address these issues. Findings. Psychological resistance often results from concerns over job displacement and skepticism toward AI, whereas organizational barriers stem from misaligned goals and entrenched cultural norms. Ethical challenges, including issues such as bias, accountability, and data privacy, add further complexity to widespread AI adoption efforts. Recommended strategies include enhancing transparency, aligning AI initiatives with organizational objectives, implementing robust governance structures, and addressing ethical concerns to improve adoption outcomes. Practical Applications. The research provides actionable guidance for business leaders and policymakers, such as encouraging open communication, investing in employee skill development, and maintaining ethical practices. These recommendations are vital for fostering trust and securing stakeholder support. Original Contribution. The study introduces an innovative framework that combines psychological, organizational, and ethical dimensions to address resistance to AI. By blending theoretical analysis with practical approaches, it empowers organizations to harness AI's transformative potential while respecting societal and moral values.
Keywords: AI technologies; ecosystems; business; modern business ventures; business management; computer technologies